Number-theoretic methods in cryptology : first international conference, NuTMiC 2017, Warsaw, Poland, September 11-13, 2017, Revised Selected Papers /: first international conference, NuTMiC 2017, Warsaw, Poland, September 11-13, 2017, Revised Selected Papers. ([2018]) - Unknown
No abstract available